A proposta curricular para a educação infantil da Paraíba e suas relações com as DCNEI e a BNCC-EI - Oliveira, Ivanilda Dantas de (2022)
Curriculum policies for Early Childhood Education - demanded after the promulgation of the Federal Constitution (1988) - were materialized amidst clashes and disputes about the function of this stage of Basic Education, bringing as dissenting developments in relation to the foundations that should guide the education of children. children aged 0 to 6 years. Imbued with this understanding, we list as main objective to analyze how the political and pedagogical foundations that guide the DCNEI affect the BNCC-EI and the Curricular Proposal of Paraíba- EI. We assume as a thesis that the assumptions of the DCNEI, despite being claimed in the texts of the BNCC-EI and the Curriculum Proposal of Paraíba-EI, do not constitute their foundations. We chose, therefore, for qualitative research aligned with the interpretive social paradigm, as we privilege the analysis of the speeches of the interviewed subjects, as well as the socio-historical-political and pedagogical contexts that shaped the process of construction of the aforementioned curricular policies, in order to unveil the implicit assumptions, conflicts, oppositions and arrive at an enriched understanding of the researched social phenomenon. To this end, we carried out a literature review about mandatory curriculum policies for Early Childhood Education and, at the same time, we undertook a documentary and empirical research. In the latter, we chose as research subjects 1 (one) representative of the management committee and 4 (four) of the technical assistance who worked in the elaboration of the Curriculum Proposal of Paraíba-EI. The organization of the collected data followed the guidelines of Content Analysis based on Bardin's meaning, through thematic categorical analysis. The results of the documentary research indicate that the DCNEI review process (2009) had an expanded participation of public actors and social movements, which, through discussions and negotiations, built consensus in relation to the concepts that should guide the Proposals Pedagogical/Curriculum of day care centers and preschools across the country. On the other hand, the political conjuncture in which the process of elaboration of the BNCC-EI and the Curricular Proposal of Paraíba-EI took place highlighted the hegemony of the Movimento pela Base and its intellectuals, which shaped a national curriculum that subordinates the formation of children to the market logic. In relation to the assumptions of the aforementioned policies, the DCNEI (2009) present coherence between the conception of child, Early Childhood Education, pedagogical proposal and curriculum, according to the emancipatory education project defended. Differently, in the documents of the BNCC-EI and the Curricular Proposal of Paraíba-EI, such conceptions are used to validate the discourse of continuity of fundamentals in relation to the DCNEI, but these are not the basis of the curricular arrangement, assuming central competences and abilities, the learning and development objectives and learning syntheses, as they allow the control of what is taught to children and the regulation of teaching work. Thus, we point out the need for institutions to claim their autonomy in the formulation of their pedagogical political project and their curricular document. However, to achieve this end, it is necessary to invest in the continuing education of Early Childhood Education teachers from the perspective of the integral development of the child, thus dissociating itself from the process of building competences, abilities and objectives. of learning proposed in the BNCC-EI and in the Curricular Proposal of Paraíba-EI, as these do not even guarantee the learning rights.